Determinants in Used Car Purchase Results - Hakim, El Ashar; Zaki, Yusuf A.; Labib, M. Fauzan; Arafa, M. Fikri; P,, Andhika Hardiman (CV. Publikasi Indonesia, 2024)
The automotive industry in Indonesia continues to experience rapid growth amidst intense competition among companies to create flagship products. This development is spurred by various factors, including lifestyle changes and the increased social status of the population. This research investigates the factors influencing the decision to purchase used cars in Jakarta, particularly among individuals aged 18-40. The automotive industry in Indonesia is undergoing rapid growth driven by lifestyle developments, increased community mobility, and enhanced social status. The purchase of used cars has become an intriguing phenomenon in the dynamics of the automotive industry, with consumers influenced by economic considerations, diversity in model and brand choices, and individual preferences. The respondents in this study are individuals aged 18-40 who are interested in purchasing used cars in Jakarta. A survey method is employed to collect data, with questionnaires distributed to randomly selected respondents. Data analysis is conducted to identify the key factors influencing the decision to purchase used cars. Purchasing used cars is an interesting phenomenon observed in the dynamics of the automotive industry. Consumers in this purchasing process are influenced by several factors, including economic considerations such as affordable prices and lower depreciation values compared to new cars. Additionally, the diversity of model and brand choices is also an important consideration for consumers when choosing used cars. The findings of this research are expected to provide deeper insights into the preferences and needs of consumers when buying used cars in Jakarta. These findings can serve as a guide for used car manufacturers and the automotive industry as a whole in designing more effective